Crude Palm Oil Price Forecasting: Box-Jenkins Approach - Mohd Arshad, Fatimah; A. Ghaffar, Roslan (1986)
A univariate ARIMA model developed by Box-jenkins was utilised to forecast the short-run monthly price of crude palm oil. The appropriate model for forecasting was found to be (0, 2, 1) (0, 1, 1) 6' This model indicates that the original crude palm oil series is non-stationary and contains some elements of multipliCity, hence inheriting moving average process. The identified ARIMA model induced the data series into a stochastic one, making it a suitable model for forecasting crude palm oil prices in the short term.